2023
DOI: 10.1371/journal.pone.0278620
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategy among the women with metastatic breast cancer attending a palliative care unit of a tertiary care hospital of Bangladesh

Abstract: Background Breast cancer is one of the leading cancers among the Bangladeshi women. Coping helps these patients to adjust with this life-changing disease. Each individual has unique and different coping mechanism. But we know a little regarding their coping strategies. This study aims to explore the different coping strategies adopted by the women with metastatic (stage IV) breast cancer attending the palliative care unit and their relationship with the common mental health issues like anxiety and depression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Also, patients who actively performed religious rituals and had affiliations with religious/spiritual communities scored higher on the Global SWB scale. In a previous study among Bangladeshi breast cancer patients, it was found that religion is the most commonly adopted coping mechanism by advanced cancer patients [ 29 ]. Religion plays an important role in spiritual coping.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients who actively performed religious rituals and had affiliations with religious/spiritual communities scored higher on the Global SWB scale. In a previous study among Bangladeshi breast cancer patients, it was found that religion is the most commonly adopted coping mechanism by advanced cancer patients [ 29 ]. Religion plays an important role in spiritual coping.…”
Section: Discussionmentioning
confidence: 99%
“…A partir da revisão dos artigos, Ranieri et al (2022) 2023), as mulheres à medida que aceitam as alterações corporais de forma positiva, conseguem ter uma melhor aceitação de autoimagem corporal, proporcionando a elas continuar a terem uma vida e relacionamentos saudáveis. E quanto a este enfrentamento a aceitação da realidade dos resultados é comum, apesar de ainda haver grupos de mulheres com CA de mama que insistem na persistência de negação do diagnóstico e não adesão terapêutica, por medo, insegurança ou por vezes, a falta de apoio, que acaba dificultando a adesão ao tratamento, promovendo adversidades da patologia (ISLAM et al, 2023).…”
Section: Discussionunclassified
“…Many studies have been conducted to assess whether illness denial was a determinant of health attitudes and behavior in patients with cancer [1, 28,[130][131][132][133][134][135][136][137][138][139][141][142][143][144][145][146][147][148] [1, 28,[130][131][132][133][134][135][136][137][138][139][141][142][143][144][145][146][147][148]. In particular, Lynch and Krush [138] showed that factors contributing to delay (defined as an interval of 3 months or longer between the time an individual first notices signs or symptoms of cancer and the time he/she seeks medical attention) in a heterogeneous sample of patients with various forms of cancer included attitudes of denial.…”
Section: Health Attitudes and Behaviormentioning
confidence: 99%